Foreign direct investment spillovers : what can we learn from portuguese data? - Flôres Jr., Renato G. (2022)
This paper investigates the impact of foreign direct investment on the productivity performance of domestic firms in Portugal. The data comprise nine manufacturing sectors for the period 1992-95. Relatively to previous studies, model specification is improved by taking into consideration several aspects: the influence of the "technological gap" on spill-overs diffusion and the choice of its most appropriate interval; sectoral variation in the coefficients of the spill-overs effect; identification of constant, idiosyncratic sectoral factors by means of a fixed effects model; and the search for inter-sectoral positive spillover effects. The relationship between domestic firms productivity and the foreign presence does take place in a positive way, only if a proper technology differential between the foreign and domestic producers exists and the sectoral characteristics are favourable. In broad terms, spillovers diffusion is associated to modem industries in which the foreign owned establishments have a clear, but not too sharp, edge on the domestic ones. Besides, other specific sectoral influences can be pertinent; agglomerative location factors being one example.